Healthcare Analytics Made Simple Techniques in healthcare computing using machine learning and Python - Kumar, Vikas (Vik) (Packt Publishing Limited, 2018)
bAdd a touch of data analytics to your healthcare systems and get insightful outcomes/b h4Key Features/h4 ulliPerform healthcare analytics with Python and SQL /li liBuild predictive models on real healthcare data with pandas and scikit-learn /li liUse analytics to improve healthcare performance/li/ul h4Book Description/h4 In recent years, machine learning technologies and analytics have been widely utilized across the healthcare sector. Healthcare Analytics Made Simple bridges the gap between practising doctors and data scientists. It equips the data scientists' work with healthcare data and allows them to gain better insight from this data in order to improve healthcare outcomes. This book is a complete overview of machine learning for healthcare analytics, briefly describing the current healthcare landscape, machine learning algorithms, and Python and SQL programming languages.